Politics of the Meiji Press The Life of Fukuchi Gen'ichirō - Huffman, James L. (University of Hawai'i Press, 1980)
This biography introduces the young Fukuchi, in the first months after the Meiji Restoration of 1868, as a newspaper editor just beginning to write critically on social and political issues. His outspoken and politically indiscreet editorials soon made him the first journalist in history of Japan to be jailed for his writings. During the early Meiji years, he continued to grope for an ideal and a position, even joining the regime as a brash and innovative official. Only when he was independent of the government bureaucracy, however, did Fukuchi assume a position of pivotal importance. During the peak years of his career from 1874 to 1888, he demonstrated the crucial advantage enjoyed by those Japanese who had gained Western knowledge and, as editor of the Tokyo Nichi Nichi, made his most distinctive contributions to Meiji society and to journalism in Japan. Using a politically awakened press, which he had invigorated with Western techniques of journalism, Fukuchi provided the popular rationale for the course followed by the government and became the period's leading nonofficial advocate of the "gradualist" approach toward constitutional government. He also founded Japan's first "gradualist" political party. The Constitutionalist Imperial Party, during his years as an editor. Despite his great influence, Fukuchi left the press world in 1888, disappointed over failures and changing alliances, a vivid illustration of the precarious nature of leadership in a transitional period. Too long allied with the forces of innovation to become a casualty of change, however, he embarked on a new life as a writer of novels, plays, and history, and emerged in the 1890's as Japan's foremost playwright. In the life of Fukuchi Gen'ichirō is the story of a history-making figure, a man whose career embodied the response of Meiji Japan to the Western challenge of modernization, and yet a man whose personal life was inescapably subject to the tensions of an era of rapid social and political change. James Huffman's fine biography is a notable book about an exciting man, a maker and mirror of his times.